Deeply Odd : an Odd Thomas novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2013)
Odd Thomas journeys through California and Nevada after a vision about the murders of three children, an effort throughout which he befriends a series of eccentric helpers who become allies in a battle against a sociopath and a network of killers.